ISLAMIC FAMILY LAW AND SOCIAL TRANSFORMATION: A STUDY ON MARRIAGE, DIVORCE, AND INHERITANCE IN THE SHARIA SYSTEM - Cahyono, Anang Wahid (Berajah Journal, 2024)
Islamic family law plays a central role in structuring marriage, divorce, and inheritance matters within Muslim societies, balancing ethical principles with legal mandates in a rapidly changing world. This study examines how Sharia law's family regulations adapt and transform to address evolving social norms while preserving Islamic principles. Using a qualitative approach, this research analyzes primary sources, including Qur’anic verses and Hadiths, alongside modern interpretations of Islamic jurisprudence (fiqh) and legal reforms in various Muslim-majority countries. Findings reveal that, while Sharia law traditionally emphasizes responsibilities and roles within the family unit, recent reforms reflect an increasing recognition of individual rights, especially in marriage and inheritance. These adaptations respond to social demands for equity, particularly regarding women's rights and gender roles, highlighting a nuanced interplay between religious values and societal needs. This paper offers insights into the role of Islamic family law in fostering family stability and continuity while responding to modern challenges and calls for balanced frameworks that respect both tradition and contemporary values.